Analisis Prinsip–prinsip Umum Pengelolaan Keuangan Negara dan Daerah berdasakan UU No.17 Tahun 2003 - Suryadin Suryadin; Ramadoni Ramadoni; Mustamin Mustamin; Erham Erham (SENTRI: Jurnal Riset Ilmiah, 2025)
In Indonesia, such standards are formally regulated under Law Number 17 of 2003 on State Finance, which functions as the foundational legal framework for the administration of public finances at both central and regional levels. This study aims to examine and analyze the general principles of state and regional financial management as normatively formulated in Law No. 17 of 2003, as well as to assess their implementation from a legal perspective. The research adopts a normative juridical method, employing statutory and conceptual approaches to interpret legal norms and doctrines relevant to state finance law. The analysis relies exclusively on secondary legal materials, including legislation, scholarly writings, and academic studies on public financial governance. The findings indicate that Law No. 17 of 2003 establishes a coherent and comprehensive normative structure consistent with the principles of good financial governance, particularly accountability and transparency. However, the implementation of these principles remains inconsistent, especially at the regional level. The main legal obstacles identified include regulatory overlap, weak synchronization between central and regional regulations, and deficiencies in internal control mechanisms. These issues result in a formalistic application of legal norms, where compliance is largely procedural rather than substantive. Consequently, strengthening regulatory harmonization and legal coherence between central and regional frameworks is essential to ensure the effective realization of the principles mandated by Law No. 17 of 2003.